Enhancing Business Decision-Making of Purwakarta MSMEs through AI-Based Market Analysis - Warsono sudiro; Suhendri; Arlen Nawang Rachelia Arlen; Indri Yani Lasmini Indri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic development; however, they face increasing challenges in making effective business decisions due to rapidly evolving market dynamics. Artificial Intelligence (AI) has emerged as a strategic tool to enhance decision-making processes through data-driven insights. This study aims to analyze the effect of AI-based market analysis on decision-making quality and its impact on business performance among MSMEs in Purwakarta. A quantitative approach was employed using survey data from 165 MSME owners, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that AI-based market analysis significantly improves decision-making quality (β = 0.66, p < 0.001), which subsequently enhances business performance (β = 0.61, p < 0.001). Furthermore, data readiness strengthens the effectiveness of AI utilization. These findings contribute to the literature on digital transformation and provide practical insights for MSMEs in adopting AI-driven strategies.